PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL BAGI SISWA SEKOLAH DASAR - Risandi Mardanis Putri; Reza Syehma Bahtiar; Jarmani Jarmani (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the application of the Problem Based Learning Model in Social Science Subjects (IPS) for the fifth-grade students of SD Dumas Surabaya. Problem Based Learning is a learning model that focuses on students, so that the application of the problem-based learning model in the Human Interaction with the Environment material can make students more active in learning. This type of research uses descriptive qualitative research. The sample of this research is the fifth-grade students of SD Dumas Surabaya. Data collection techniques using Learning Outcomes Test, Observation, Interview Guide. The data obtained by the test of learning outcomes is to use calculations. The results of the study showed that the Learning Outcome Test at the first meeting was 76, 25%, and the second meeting was 90%.